The Hardness of Aluminum Oxide Surface in Anodized Coloring Under Low Voltage - Buwono, Haris Puspito; Hadi, Syamsul; Muzaki, Mochamad; Subagiyo, Subagiyo; Agustriyana, Lisa; Hadi, Samsul; Nurchajat, Nurchajat (Politeknik Negeri Ujung Pandang, 2019)
Coloring of aluminum oxide on the Aluminum type AA1100, which is the typical type for household appliances and purposes, through anodizing coloring process by the blue color of commercial printer ink had been successfully performed. The blue color was well adhered and was not easy to be removed by physical treatment such as wiping. The anodize coloring process includes chemical cleaning of aluminum surface, the formation of pores in the sulfuric acid solution at a specific current and a specified duration of time, coloring and closing the pores via sealing. It also shows the anodizing process increases aluminum oxide surface hardness increased by applying higher current density, and longer duration time of the process. The aluminum oxide hardness was in harmony to the duration of time processing, and current density; however, not in line to a concentration of the solution. The maximum hardness of the aluminum oxide layer obtained is 50 kg/mm2. The relation of current density and voltage, the effect of current density and sulfuric acid concentration toward aluminum oxide hardness were analyzed. Moreover, the difference of aluminum oxide hardness of the front side and backside to cathode also discussed.